2018
DOI: 10.1186/s12891-018-2155-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving results in rat fracture models: enhancing the efficacy of biomechanical testing by a modification of the experimental setup

Abstract: BackgroundAnimal fracture models, primarily performed in rats, are crucial to investigate normal and pathological bone healing. However, results of biomechanical testing representing a major outcome measure show high standard deviations often precluding statistical significance. Therefore, the aim of our study was a systematical examination of biomechanical characteristics of rat femurs during three-point bending. Furthermore, we tried to reduce variation of results by individually adapting the span of bearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
12
1
2
Order By: Relevance
“…The results of the biomechanical test showed that at the end of the recovery period of 28 days the groups treated with ghrelin had a statistically higher breaking force than the control groups. The breaking force results of the ghrelin‐treated group was as high as breaking force needed for a healthy rat femur that was reported as 116 to 251 N in the study of Prodinger et al 17 Ghrelin treatment through 28 days was shown to improve fracture healing in rat femur compared to the no‐treatment group. Compared to healthy bone, breaking distances of the fracture model groups were higher.…”
Section: Discussionmentioning
confidence: 72%
“…The results of the biomechanical test showed that at the end of the recovery period of 28 days the groups treated with ghrelin had a statistically higher breaking force than the control groups. The breaking force results of the ghrelin‐treated group was as high as breaking force needed for a healthy rat femur that was reported as 116 to 251 N in the study of Prodinger et al 17 Ghrelin treatment through 28 days was shown to improve fracture healing in rat femur compared to the no‐treatment group. Compared to healthy bone, breaking distances of the fracture model groups were higher.…”
Section: Discussionmentioning
confidence: 72%
“…Each experimental model represent different mechanisms, where bone repair of cortical perforation defects occurs by intramembranous ossification, and bone repair of fracture is the result of abundant cartilaginous callus formation followed by endochondral ossification. 3 Various experimental studies focused on the diaphysis of long bones, 1,2,4 however to evaluate biomechanical effect of bone alterations, the metaphysis of a femur or tibia should be considered, since the diaphysis of long bones consist only of cortical bone and bone marrow and major changes due to bone degenerative diseases are also observed in the trabecular bone that is located in the metaphysis. 3,5,6,7,8,9 In order to determine the effect of any therapy during the repair process of bone defects, it is essential to evaluate the structural fracture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…3 Various experimental studies focused on the diaphysis of long bones, 1,2,4 however to evaluate biomechanical effect of bone alterations, the metaphysis of a femur or tibia should be considered, since the diaphysis of long bones consist only of cortical bone and bone marrow and major changes due to bone degenerative diseases are also observed in the trabecular bone that is located in the metaphysis. 3,5,6,7,8,9 In order to determine the effect of any therapy during the repair process of bone defects, it is essential to evaluate the structural fracture resistance. Several structural parameters such as geometry, mineral content and density are used to indirectly evaluate the biomechanical properties of bone, nonetheless, bone ability to resist fracture can only be assessed by biomechanical strength tests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations